Duplex systems: Top-down or bottom-up approach?. Issue 3 (June 2020) - Keene, D.J.B.; Subramaniam, R.
Summary: Introduction: Duplex systems can be complicated by reflux, ureterocele, obstruction (most commonly PUJ in a lower moiety) and wetting secondary to an ectopic ureteric insertion in girls. The decision making algorithm for selection of surgical approach is complex and there is no consensus. The authors described the outcomes following an upper urinary tract approach in 2011(1) and now compare these results in a similar group of patients managed using a lower approach. Objectives: To assess whether a top-down or bottom-up approach results in different likelihoods for further surgery. Study design: A prospectively database was maintained for consecutive patients undergoing surgery for duplex systems by a single surgeon between 2003 and 2015. Patients were classified into 2 groups; Group 1 initial intention for upper urinary tract approach (heminephroureterectomy-HN) or Group 2 lower urinary tract approach (bladder reconstructive surgery-BRS). The requirement for further surgery was recorded-endoscopic incision (EI), bladder reconstructive surgery (BRS), endoscopic correction of reflux (ECR), heminephroureterectomy (HN). Indications for initial and subsequent surgery included urinary tract infection, VUJ obstruction and incontinence. Endoscopic incision was not performed for patients with an asymptomatic ureterocele. Statistical analysis consisted of Fisher's exact test with a 2 tail p value < 0.05 being statistically significant. Results: 79 patients underwent surgery for duplex systems. 39 patients had HN initially (Group 1) and 40 patients had BRS initially (Group 2). Further surgery was performed in 21% of patients from Group 1 (8 BRS) vs 5% of patients from Group 2 (1 redo BRS, 1 ECR). Significantly less additional surgical procedures were performed after BRS compared to HN (p = 0.048). The presence of both reflux and ureterocele increases the chances of further surgery in those patients who had HN initially compared to BRS (p = 0.01). No patients developed urinary retention or required intermittent catheterisation to improve bladder emptying. Conclusions: Bladder reconstructive surgery (BRS) reduces the requirement for further surgery compared to heminephroureterectomy (HN) in symptomatic patients with a duplex kidney and either dilating vesicoureteric reflux or ureterocele. Summary Table Group 1 –HN (Heminephroureterectomy) 2 –BRS (Bladder reconstructive surgery) Number of patients 39 40 Gender (Male: Female) M 10: F 29 M 8: F 32 Indication for initial surgery Infections 33 26 Incontinence (ectopic ureter) 2 4 Progressive hydronephrosis 4 10 Median age at surgery (years) 2.2 years (1.6–3.4) 3.4 years (1.9–6.4) Median duration of follow up (years) 11.9 (10.6–12.8) 5.6 years (4.2–7.1) Overall requirement for further surgery (%) 8 patients (21%)∗ 2 patients (5%)∗ Indication for redo surgery Infections 8 (stump infections 2, reflux to ipsilateral lower moiety 2, ureterocele dilatation 4) 1 (reflux) Incontinence 0 0 Progressive hydronephrosis 0 1 (VUJ stenosis) Nature of further surgery 21% (8 BRS) 5% (1 redo BRS, 1 ECR)